Strategi Optimalisasi Potensi Sumber Daya Lokal Melalui Pemetaan Wilayah Desa Sidowayah, Kecamatan Pancur, Kabupaten Rembang, Jawa Tengah - Roza Azizah Primatika; Praba Sultan; Affan Martadi; Eko Fibri Haryanti; Mukhammad Anwar Fu`Adi (Direktorat Pengabdian kepada Masyarakat, 2023)
Village potential is a source of regional assets that must be developed and managed well. Sidowayah Village is a village that has abundant natural resource potential. The community and policymakers need innovation in developing village potential to align government programs towards Sustainable Development Goals (SDGs). The aim of UGM KKN – PPM activities for period 2 of 2023 is to increase village potential based on local resources owned through a village infrastructure plan development strategy. The methods used in this activity are observation, interviews, and focus group discussions (FGD). The data for this activity is primary and secondary data obtained from the Sidowayah Village Village/Subdistrict Administrative Services Information System (SIMPADEK) report. The result of the KKN – PPM student activities is mapping village potential with existing local resources from agriculture, animal husbandry, and MSMEs. Increasing human resources with outreach activities for small MSME entrepreneurs and educating farmers about the importance of animal health to avoid outbreaks of infectious animal diseases. Design and planning for the development of waste disposal site infrastructure and waste transportation routes to support Sidowayah village facilities and infrastructure as the implementation of strategies to increase village potential.